TIMP3 Overexpression Improves the Sensitivity of Osteosarcoma to Cisplatin by Reducing IL-6 Production - Han, Xiu-guo; Mo, Hui-min; Liu, Xu-qiang; Li, Yan; Du, Lin; Qiao, Han; Fan, Qi-ming; Zhao, Jie; Zhang, Shu-hong; Tang, Ting-ting (Frontiers in Genetics, 2018)
Osteosarcoma is the most common bone cancer in children and adolescents. Tissue inhibitors of metalloproteinases (TIMPs)-3 inhibit matrix metalloproteinases to limit extracellular matrix degradation. Cisplatin is a widely used chemotherapeutic drug used to cure osteosarcoma. Interleukin (IL)-6 and TIMP3 play important roles in the drug resistance of osteosarcoma; however, their relationship in this process remains unclear. This study aimed to explore the role of TIMP3 in the cisplatin sensitivity of osteosarcoma and its underlying molecular mechanisms in vitro and in vivo. We compared TIMP3 expression levels between patients with cisplatin-sensitive and -insensitive osteosarcoma. TIMP3 was overexpressed or knocked down in the Saos2-lung cell line, which is a Saos2 subtype isolated from pulmonary metastases that has higher cisplatin chemoresistance than Saos2 cells. IL-6 expression, cell proliferation, sensitivity to cisplatin, migration, and invasion after TIMP3 overexpression or knockdown were determined. The same experiments were performed using MG63 and U2OS cells. Subsequently, luciferase-labeled Saos2-lung cells overexpressing TIMP3 were injected into the tibiae of nude mice treated with cisplatin. The results showed that IL-6 inhibited TIMP3 expression in Saos2 and Saos2-lung cells via signal transducer and activator of transcription 3 (STAT3) activation. STAT3 knockdown reversed the effect of IL-6. The expression of TIMP3 was higher in patients with cisplatin-sensitive osteosarcoma than in those with insensitive osteosarcoma. IL-6 expression was downregulated upon TIMP3 overexpression, and upregulated by TIMP3 knockdown. TIMP3 overexpression suppressed cell proliferation and enhanced cisplatin sensitivity by activating apoptosis-related signal pathways and inhibiting IL-6 expression in vitro and in vivo. In conclusion, cisplatin sensitivity correlated positively with TIMP3 expression, which is regulated by the IL-6/TIMP3/caspase pathway. The TIMP3 pathway could represent a target for new therapies to treat osteosarcoma.